Analysis of the First‐ and Second‐Generation Raving Dragon Novelty Bath Salts Containing Methylone and Pentedrone1. (2nd December 2014) - Poklis, Justin L.; Wolf, Carl E.; ElJordi, Omar I.; Liu, Kai; Zhang, Shijun; Poklis, Alphonse
Abstract: In recent years, a large number of designer drugs sold as "Bath Salts" have appeared on the market. In July of 2011, Raving Dragon Novelty Bath Salts was obtained over the Internet. This product became unavailable in October of that year coinciding with the DEA issuing a temporarily schedule of mephedrone, methylone, and MDPV. Four months later in February of 2012, a new product was released from the same company under the new name Raving Dragon Voodoo Dust. The contents of both products were identified using spectroscopy methods: nuclear magnetic resonance, infrared, UV–visible, tandem mass spectrometry, and high‐resolution time‐of‐flight mass spectrometry. It was determined that Raving Dragon Novelty Bath Salts contained methylone. The replacement product Raving Dragon Voodoo Dust contained the unscheduled drug pentedrone. The Raving Dragon brand of products illustrates the rapid change of ingredients in these products to circumvent laws restricting availability, distribution, and use.